Projective resolution of irreducible modules over tiled order - Zhuravlev, V.; Zhuravlyov, D. (Algebra and Discrete Mathematics, 2012)
We indicate the method for computing the kernels of projective resolution of irreducible module over tiled order. On the base of this method we construct projective resolution of irreducible module and calculate the global dimension of tiled order. The evident view of kernels of projective resolution allows to check easily the regularity of tiled order.